(untitled) (Tokyo, 1981)
Facts about robots and their significance in the Japanese economy
Keywords: Automation,Robots, Industrial,Tự động hóa,Robot, công nghiệp; Economic aspects,Khía cạnh kinh tế; Japan,Japan,Nhật Bản,Nhật Bản